2012
DOI: 10.1136/tobaccocontrol-2012-050600
|View full text |Cite
|
Sign up to set email alerts
|

Change in tobacco excise policy in Bulgaria: the role of tobacco industry lobbying and smuggling

Abstract: Please cite only the published version using the reference above.See http://opus.bath.ac.uk/ for usage policies.Please scroll down to view the document.i Paper title:Change in tobacco excise policy in Bulgaria: the role of tobacco industry lobbying and smuggling Authors:Skafida, V (1); Silver, K E (2); Rechel, B P D (3); Gilmore, A (4) AcknowledgementsThe authors would like to thank Katherine Smith and Simon Williams for conducting initial exploratory searches for the report, and Cathy Flower for her administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 27 publications
4
28
0
Order By: Relevance
“…''My impression of MNEs [is] that they try and play by the rules but over time they adapt to local practices,'' points out a local business executive (BULGARIA-2). By way of corroboration of our interviewee's observation, Skafida, Silver, Rechel, and Gilmore (2014) find that international tobacco companies replicate the practices of local firms and even engage in tobacco smuggling. In Poland in 2014, the local anti-corruption agency unveiled a massive corruption scandal that involved major multinational IT companies, including Hewlett Packard (HP).…”
Section: Differences In Risk Profilesupporting
confidence: 57%
“…''My impression of MNEs [is] that they try and play by the rules but over time they adapt to local practices,'' points out a local business executive (BULGARIA-2). By way of corroboration of our interviewee's observation, Skafida, Silver, Rechel, and Gilmore (2014) find that international tobacco companies replicate the practices of local firms and even engage in tobacco smuggling. In Poland in 2014, the local anti-corruption agency unveiled a massive corruption scandal that involved major multinational IT companies, including Hewlett Packard (HP).…”
Section: Differences In Risk Profilesupporting
confidence: 57%
“…More broadly, our findings, combined with what is already known about historical TTC involvement in the illicit tobacco trade,1–6 concerns that this involvement may be ongoing,43–45 53 overwhelming evidence of the TTCs’ efforts to undermine the science supporting tobacco control56 and growing evidence that industry data on illicit (including its EPSs) are misleading,27 36 raise serious questions about the appropriateness of PMI's role in PS. Concerns about the EU deals with industry on illicit have previously been raised,57 but have yet to be adequately addressed despite growing evidence that the tobacco industry sees the illicit trade as a means of securing access to and influence over regulators and undermining Article 5.3 26 58 59.…”
Section: Discussionmentioning
confidence: 72%
“…The articles cited in Project Star are as follows (the sources for the data given within each article are italicised):

On smoke-free legislation: no data on illicit.

http://tobaccoreporter.com/home.php?id=498&art=2424: A third of the tobacco products sold in Bulgaria are illicit, according to a Novinite story quoting sources within Bulgartabac .

http://www.novinite.com/view_news.php?id=111533: Opponents to the tax hike claim that it will boost cigarette smuggling and may lead to the bankruptcy of the dominant state cigarette maker Bulgartabak.

Trud Daily: unable to obtain.

http://www.stumbleupon.com/su/3Urbja/www.tobacco-news.net/bulgarias-new-cigarette-prices-come-into-force: No data but ‘Tobacco business representatives have criticised the idea of raising the excise duty, saying that it would only stimulate contraband and will not bring the expected revenue to the Budget’.

http://www.novinite.com/view_news.php?id=114806: Almost identical to (3) above. States ‘ Opponents to the tax hike claim that it will boost cigarette smuggling and may lead to the bankruptcy of the dominant state cigarette maker Bulgartabak.’

http://sofiaecho.com/2011/01/19/1027294_bulgaria-to-introduce-complete-ban-on-smoking-in-small-cafes-in-mid-2011: ‘The decision was immediately opposed by small-size businesses, which said that the new restriction would produce a wave of bankruptcies.’ http://www.novinite.com/view_news.php?id=106476: ‘One third of the tobacco products in Bulgaria are sold on the black market according to state owned tobacco monopoly Bulgartabac .’
Recent research on tobacco industry conduct in Bulgaria43 highlights that the figures the industry uses in its discourse and lobbying on illicit tobacco in the country exaggerate the extent of the problem when compared with independent sources and yet industry figures feature prominently in press coverage. For example, an industry representative claimed in 2007 that planned excise increases would raise smuggling by around 20%,74 although an independent survey indicated that a hypothetical 20% increase in price would prompt only 11.2% of smokers to switch to smuggled cigarettes75 and the excise increase that was implemented (ultimately in 2008) increased weighted average prices by only 8% 76…”
Section: A Review Of the Ps Methodologymentioning
confidence: 99%
“…The information was disseminated directly at schools and Catholic parishes, and the industry even organised workshops for customs officers 31. Additionally, since the industry estimates have been used by market intelligence firms,34 these inflated figures have been disseminated to other important stakeholders and repeated in many market analyses.…”
Section: Discussionmentioning
confidence: 99%